Accumulation and efficiency of nutrient use in crop systems in second crop under no-tillage - Dalla Cort, Andressa Selestina [UNESP]; Feitosa, Priscilla Barros; Pacheco, Leandro Pereira; Greco, Tassia Maira; Ferreira Silva, Ivan David; Souza, Edicarlos Damacena de; Santos, Leticia Ferreira; Petter, Fabiano Andre; Costa Crusciol, Carlos Alexandre [UNESP] (Empresa Brasil Pesq Agropec, 2021)
The objective of this work was to evaluate phytomass production, nutrient cycling, and efficiency of nutrient use by single and intercropped crop systems, in the second crop, under no-tillage. The experiment was carried out during the second crop of 2014 and 2015 in the Cerrado biome of the state of Mato Grosso, Brazil, in a randomized complete block design, with nine treatments and four replicates. In 2014, the systems were evaluated at 63, 93, 124, and 157 days after sowing; and, in 2015, they were evaluated at flowering and senescence. The concentrations of nitrogen, phosphorus, potassium, calcium, and magnesium were determined. In 2014, the single crop systems Urochloa ruziziensis, Cajanus cajan, and Pennisetum glaucum showed the largest accumulations of phytomass and nutrients. In 2015, the intercropped systems showed the largest accumulations of phytomass, the largest nutrient cycling, and the highest nutrient use efficiency. In the no-tillage crop systems, U. ruziziensis, either in single cultivation or intercropped with corn and sunflower, increased phytomass. The most efficient systems for the use of all nutrients, in the Cerrado of Mato Grosso, are the intercropping of sunflower with U. ruziziensis, corn with U. ruziziensis, and corn with Crotalaria spectabilis.
Keywords: Cerrado; cover crop; macronutrient; nutrient cycling; soybean